2018
DOI: 10.1002/jbm.b.34080
|View full text |Cite
|
Sign up to set email alerts
|

Core/shell cellulose‐based microspheres for oral administration of Ketoprofen Lysinate

Abstract: Herein, we propose the fabrication of a new carrier with core/shell structure-inner core of cellulose acetate (CA) coated by a micrometric layer of chitosan (CS)-fabricated through an integrated process, which combines Electro Dynamic Atomization (EDA) and layer-by-layer (LbL) technique. We demonstrate that CA based microspheres possess a unique capability to relevantly retain the drugs-that is, Ketoprofen Lysinate (KL)-along the gastric tract, while providing a massive release along the intestine. CS shell sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…It has proven to be possible to perform the electrospinning process even when one or more of the working fluids cannot on its own be processed: For instance, in modified coaxial electrospinning, a spinnable core solution is partnered with an unspinnable sheath fluid. These novel processes permit the production of nanofibers with increasingly complicated nanostructures [32,33,34,35,36,37]. As a result, in the literature, there are numerous publications that explore the influence of a single parameter on the nanofibers or nanostructures prepared by electrospinning, elucidating relationships for manipulating the products (mainly in terms of diameter, but also for other properties such as morphology, surface smoothness and the details of the nanostructure) [38,39,40,41,42,43].…”
Section: Introductionmentioning
confidence: 99%
“…It has proven to be possible to perform the electrospinning process even when one or more of the working fluids cannot on its own be processed: For instance, in modified coaxial electrospinning, a spinnable core solution is partnered with an unspinnable sheath fluid. These novel processes permit the production of nanofibers with increasingly complicated nanostructures [32,33,34,35,36,37]. As a result, in the literature, there are numerous publications that explore the influence of a single parameter on the nanofibers or nanostructures prepared by electrospinning, elucidating relationships for manipulating the products (mainly in terms of diameter, but also for other properties such as morphology, surface smoothness and the details of the nanostructure) [38,39,40,41,42,43].…”
Section: Introductionmentioning
confidence: 99%
“…This has allowed the containment of capsule elongation, also influencing specific functionalities for a controlled release of anti-inflammatory drugs. Recent studies have demonstrated the versatility and high feasibility of the EHDA process to particularize properties and functions of micro-sized devices by the easy customization of the process setup configuration, in order to obtain tailored systems for different applications in biomedical areas (i.e., regenerative medicine, drug delivery, bio-cosmetics, bio-packaging) [17,24] that are easily scalable for industrial production [25].…”
Section: Resultsmentioning
confidence: 99%
“…In vitro release tests were conducted onto KL-loaded systems in simulated biological fluids, simulating different pH conditions along the gastro-digestive tract. Hence, simulated gastric fluids (SGF) and intestinal fluids (SIF) were prepared according to the European guidelines of pharmacopoeia, in accordance with previous studies [17]. Samples were placed into 1 mL of medium and incubated at 37 °C under shaking.…”
Section: Methodsmentioning
confidence: 99%
“…In this way, the recent customization of electrohydrodynamic processes may offer new opportunities to use polymeric solutions or slurries in a wider range of viscosities [ 127 ]. As a function of the solution properties, it is possible to control the drop formation assisted by the electrical forces, not only to generate continuous patterns but also to confine cellulose materials in micro or nanosized units with highly customizable surface area [ 128 , 129 ] suitable for the fabrication of innovative Ag release systems.…”
Section: Preparation Methods For Cellulose/silver Nanocompositesmentioning
confidence: 99%